NO2 Sensing Characteristics of Si MOSFET Gas Sensor Based on Thickness of WO3 Sensing Layer - Jeong, Yujeong; Hong, Seongbin; Jung, Gyuweon; Jang, Dongkyu; Shin, Wonjun; Park, Jinwoo; Han, Seung Ik; Seo, Hyungtak; Lee, Jong Ho (Journal of Sensor Science and Technology, 2020)
This study investigates the nitrogen dioxide (NO2) sensing characteristics of an Si MOSFET gas sensor with a tungsten trioxide (WO3) sensing layer deposited using the sputtering method. The Si MOSFET gas sensor consists of a horizontal floating gate (FG) interdigitated with a control gate (CG). The WO3 sensing layer is deposited on the interdigitated CG-FG of a field effect transistor (FET)-type gas sensor platform. The sensing layer is deposited with different thicknesses of the film ranging from 100 nm to 1 μm by changing the deposition times during the sputtering process. The sensing characteristics of the fabricated gas sensor are measured at different NO2 concentrations and operating temperatures. The response of the gas sensor increases as the NO2 concentration and operating temperature increase. However, the gas sensor has an optimal performance at 180°C considering both response and recovery speed. The response of the gas sensor increases significantly from 24% to 138% as the thickness of the sensing layer increases from 100 nm to 1 μm. The sputtered WO3 film consists of a dense part and a porous part. As reported in previous work, the area of the porous part of the film increases as the thickness of the film increases. This increased porous part promotes the reaction of the sensing layer with the NO2 gas. Consequently, the response of the gas sensor increases as the thickness of the sputtered WO3 film increases.
Keywords: FET-type; Gas sensors; NO2 gas; RF magnetron sputtering; WO3